CD31 regulates metastasis by inducing epithelial–mesenchymal transition in hepatocellular carcinoma via the ITGB1-FAK-Akt signaling pathway. (10th August 2018) - Zhang, Yuan-Yuan; Kong, Ling-Qun; Zhu, Xiao-Dong; Cai, Hao; Wang, Cheng-Hao; Shi, Wen-Kai; Cao, Man-Qing; Li, Xiao-Long; Li, Kang-Shuai; Zhang, Shi-Zhe; Chai, Zong-Tao; Ao, Jian-Yang; et al.
Abstract: Platelet endothelial cell adhesion molecule-1 (PECAM-1 or CD31) is a well-known marker of endothelial cells and a key factor for adhesion and accumulation of platelets. CD31 plays roles in cell proliferation, apoptosis, migration, and cellular immunity. CD31 is also expressed on tumor cells, such as breast cancer cells and non-Hodgkin's lymphomas, and contributes to tumor cell invasion. Here, our experiments show that CD31 promotes metastasis by inducing the epithelial–mesenchymal transition in hepatocellular carcinoma by up-regulating integrin β1 via the FAK/Akt signaling pathway. Highlights: CD31 is expressed on tumor cells of hepatocellular carcinoma and is correlated with a reduced OS and DFS. CD31 promotes tumor metastasis in hepatocellular carcinoma by inducing epithelial–mesenchymal transition. The ITGB1-FAK-Akt signaling pathway is critical for CD31 to induce epithelial–mesenchymal transition. The CD31 positive tumor cells form a new subgroup of HCC and may provide a new insight into abnormal differentiation of HCC cells.